Results of an online community survey on cyclist's riding and racing habits, crash history, traumatic and chronic injury, and medical treatment - Meyers, A. C.; Bhatnagar, S.; Robidoux, G.; Kotler, D. (Journal of Science and Cycling, 2017)
Cycling is an increasingly popular activity, mode of transportation, and sport, with a growing body of literature on all three of these aspects. Research on injury risk and rate has been highly focused on localities or population subsets. We hypothesized that there would be no relationship between gender and any study variable (riding habits, racing, crash history, etc). This was an online-survey design study. We aimed to add to the literature by using an online, self-reporting questionnaire regarding riding habits, crash history, and traumatic and overuse injury history. 785 people completed the survey. The majority were road cyclists, and nearly half of respondents were active racers. 51.7% of respondents reported a crash in the 2 years prior to taking the survey, and 23.5% reported chronic discomfort when riding. Of those with traumatic or overuse injury, 84.5% and 63.1%, were satisfied with the medical care for that injury, respectively. Researchers and clinicians need to work together to investigate factors that impact riding habits, crash and injury incidence, and outcomes of medical care. Cyclists have complex medical needs that are not always adequately addressed by medical providers, particularly in the spectrum of overuse injury. We identify several gaps in cycling research and lay the groundwork for future questions that will contribute to the literature in the areas of medicine and cycling.